Depyridination Mechanism and Non-isothermal Kinetics of (μ-2-Nitrobenzoato-κ2O:O´)bis-[(pyriden-κN)zinc(II) - LI, HUA-QIONG; ZHAO, GUOLIANG (Asian Journal of Chemistry, 2010)
Thermal depyridination mechanism and the non-isothermal kinetics of (μ-2-nitrobenzoato-κ2O:O')bis-[(pyriden-κN) zinc(II)] was studied by TG method. The decomposition residue of this complex was characterized by XRD. The data from non-isothermal experiments were analyzed by Achar and the improved Ozawa methods. It was found that the depyridination process is governed by three-dimensional diffusion (spherical symmetry, 2D3) and the kinetic equation is 3/2(1-α)2/3[1-(1-α)1/3]-1.